2021
DOI: 10.1038/s41598-020-80100-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water immersion on vection in virtual reality

Abstract: Research about vection (illusory self-motion) has investigated a wide range of sensory cues and employed various methods and equipment, including use of virtual reality (VR). However, there is currently no research in the field of vection on the impact of floating in water while experiencing VR. Aquatic immersion presents a new and interesting method to potentially enhance vection by reducing conflicting sensory information that is usually experienced when standing or sitting on a stable surface. This study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…Moreover, potential objective indicators of vection, for example, electroencephalography, electrocardiograms, eye tracking, galvanic skin response or measurements of postural sway should be recorded concurrently and be detailed. Additional to vection intensity measures, motion sickness and presence should be measured and reported upon (e.g., see D' Amour et al, 2017;Fauville et al, 2021). Lastly, participants should be briefly qualitatively interviewed about their experience of the vection experiment to help re-evaluate whether the definition or description of vection matched participants' sensory experience during the experiments (e.g., see Soave et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, potential objective indicators of vection, for example, electroencephalography, electrocardiograms, eye tracking, galvanic skin response or measurements of postural sway should be recorded concurrently and be detailed. Additional to vection intensity measures, motion sickness and presence should be measured and reported upon (e.g., see D' Amour et al, 2017;Fauville et al, 2021). Lastly, participants should be briefly qualitatively interviewed about their experience of the vection experiment to help re-evaluate whether the definition or description of vection matched participants' sensory experience during the experiments (e.g., see Soave et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of HMDs has shown to be more immersive compared to screen-based methods (Shu et al, 2019), simulators utilizing HMDs are more likely to elicit CS due to this inherent rendering lag, which could negatively impact simulator fidelity. A review by Weech et al (2019) concluded that there appears to be a negative relationship between presence and CS, and the authors highlighted the need to measure vection, CS and presence concurrently (e.g., see D 'Amour et al, 2017;Fauville et al, 2021). Thus, it is worthwhile investigating if, and how, multisensory stimulation can elicit the appropriate (illusory) sensation of self-motion in a high-fidelity environment with the lowest probability of eliciting MS/CS.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we found additional effects only in the Parabolic flight experiment, where not only proprioception (affected during both microgravity 20 and water immersion 21 ), but also the vestibular system is perturbed 22 , 23 . Indeed, our vestibular system, which evolved to optimally work on ground in a 1 g environment, provides us with erroneous or disorienting information in microgravity conditions, where proprioceptive and vestibular signals 24 become unreliable sources of information.…”
mentioning
confidence: 70%